Plato's Cratylus : The Comedy of Language - Ewegen, S. Montgomery (Book collections on Project MUSE., 2014)
Plato's dialogue Cratylus focuses on being and human dependence on words, or the essential truths about the human condition. Arguing that comedy is an essential part of Plato's concept of language, S. Montgomery Ewegen asserts that understanding the comedic is key to an understanding of Plato's deeper philosophical intentions. Ewegen shows how Plato's view of language is bound to comedy through words and how, for Plato, philosophy has much in common with playfulness and the ridiculous. By tying words, language, and our often uneasy relationship with them to comedy, Ewegen frames a new reading of this notable Platonic dialogue.